Multi-level porous iron-based catalyst and its preparation method and application
The multi-stage porous iron-based catalyst was synthesized by template method and hydrothermal synthesis method, and the existing iron-based catalysts were solved, and efficient methane selectivity and catalyst stability were achieved.
Patent Information
- Application Number
- CN202310106538.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-13
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-02-13
AI Technical Summary
The existing iron-based catalysts are less selective during methanation and are prone to inactivate due to loss of active metals or the sintering effect of the carrier, increasing the cost of industrial production.
Iron hydroxide composite crystals were synthesized by template method and hydrothermal synthesis method, and high-temperature calcination was carried out to convert them into multi-stage porous iron-based catalysts, forming a unique multi-stage pore structure with template agents as the main framework structure, improving the selectivity of methane.
The selectivity of methane is significantly improved, the diffusion rate of reactants and products is improved, and the generation rate of carbon deposits is reduced, thereby improving the stability of the catalyst.
Smart Images

Figure CN116060008B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy chemical industry, and specifically relates to a multi-level porous iron-based catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, the development and utilization of coal, oil, natural gas, etc. has greatly promoted the development of social economy and the progress of science and technology, but it has also led to a surge in the content of carbon dioxide in the atmosphere. Faced with the increasingly severe pressure of CO2 emission reduction and the huge carbon emission trading market, how to efficiently utilize CO2 resources has become a hot topic in C1 chemistry research (Chemical Industry and Engineering Journal, 2017, 68(4):1282-1285). At present, carbon dioxide methanation has attracted the attention of many scholars. Carbon dioxide methanation can use abundant CO2 as a carbon source, which not only helps to reduce greenhouse gas emissions but also can be used as an energy carrier for chemical storage of excess electricity.
[0003] In many current studies, nickel is considered to be CO x Active substances for methanation, in addition to other Group 8-10 metals, most notably Ru, Rh, Co, and Fe, also have good activity in the methanation process. However, one of the disadvantages of traditional nickel-based catalysts is the highly toxic and volatile nickel carbonyl formed during the catalytic reaction. Due to the high toxicity of nickel carbonyl, special recovery technology is required for waste catalysts, which increases the cost of industrial production; nickel carbonyl will cause the nickel-based catalyst to be deactivated due to the loss of active metals or reduced activity, and the sintering effect of the carrier will also cause the deactivation of the nickel-based catalyst. Therefore, the nickel-based catalyst needs to be subjected to harsh hydrothermal conditions for methanation reaction.
[0004] It is well known that iron-based catalysts are very active in syngas reactions, such as the synthesis of NH3 and the production of hydrocarbons through Fischer-Tropsch synthesis. Iron-based catalysts also show good catalytic activity in water gas reforming reactivity. However, current research on iron-based catalysts mainly focuses on how to improve the comprehensive yield of hydrocarbon products, while there are few reports on how to improve methane selectivity. Summary of the invention
[0005] In view of this, it is necessary for the present invention to provide a multi-level porous iron-based catalyst and a preparation method and application thereof to solve the above problems.
[0006] Specifically, the technical solution provided by the present invention is: a method for preparing a multi-level porous iron-based catalyst, comprising the steps of:
[0007] Synthesizing ferric hydroxide composite crystals, using soluble iron salt as raw material, adopting template method and hydrothermal synthesis method to synthesize ferric hydroxide composite crystals;
[0008] Calcination treatment: firstly grind the iron hydroxide composite crystals, and then perform high-temperature calcination treatment to convert the iron hydroxide therein into iron oxide, so as to obtain a hierarchical porous iron-based catalyst.
[0009] The "iron-based catalyst" mentioned in this article mainly refers to the ferric oxide catalyst, and the "iron hydroxide composite crystal" refers to a substance that can form ferric oxide after high-temperature calcination, such as ferric hydroxide.
[0010] Based on the above method, the step of synthesizing the iron hydroxide composite crystals includes: first uniformly mixing the template, the soluble iron salt and the precipitant in an aqueous solution to form an iron hydroxide suspension; then placing the iron hydroxide suspension in a hydrothermal reactor to undergo a crystallization reaction at 150°C to 240°C to obtain iron hydroxide composite crystals, which are mainly composed of a template and porous iron hydroxide surrounding the template. Based on the above method, the step of forming the iron hydroxide suspension includes: first dissolving the template in deionized water to form a template suspension; dropping the soluble iron salt and the precipitant into the template suspension and uniformly mixing to form the iron hydroxide suspension. Based on the above method, after the iron hydroxide suspension undergoes a crystallization reaction in the hydrothermal reactor, it is filtered, separated, washed, and dried in sequence to obtain the iron hydroxide composite crystals.
[0011] Based on the above method, the calcination treatment step includes: first grinding the iron hydroxide composite crystal into powder to obtain a precursor powder, then placing the precursor powder in a muffle furnace, and calcining it at 550°C to 700°C for 4 to 9 hours to convert the iron hydroxide therein into iron oxide, thereby obtaining the multi-level porous iron-based catalyst.
[0012] Based on the above method, it also includes the step of grinding and granulating the multi-level porous iron-based catalyst, passing it through an 80-120 mesh sieve, and obtaining multi-level porous iron-based catalyst particles with a particle size of 80-120 mesh.
[0013] The present invention also provides a multi-level porous iron-based catalyst prepared by the above method, which comprises an iron oxide body and a pore structure penetrating the iron oxide body, wherein the average pore size of the pore structure is less than 15 nm, and the pore size is concentrated in 5-14 nm.
[0014] Preferably, the pore volume density of the multi-level porous iron-based catalyst is 0.1 to 0.3 cm 3 / g; the specific surface area of the multi-level porous iron-based catalyst is 50 to 70 m 2 / g.
[0015] The present invention also provides an application of the multi-level porous iron-based catalyst in the preparation of methane. Specifically, the multi-level porous iron-based catalyst is mainly used as a catalyst for preparing methane.
[0016] Based on the above application, the multi-level porous iron-based catalyst is used in preparing methane using carbon dioxide and hydrogen as raw materials.
[0017] Therefore, compared with the prior art, the above-mentioned multi-level porous iron-based catalyst provided by the present invention is based on the traditional iron-based catalyst, and a template agent is introduced to form a composite crystal of iron hydroxide, and the composite crystal of iron hydroxide is converted into an iron oxide body by high-temperature calcination, and the template agent is volatilized by high-temperature carbonization to form a gas, and a unique multi-level pore structure with the template agent as the main skeleton structure is formed in the iron oxide body; the shape of the pore structure and its pore size limit the generation of high-carbon molecules, thereby greatly improving the selectivity of methane. In addition, the special pore structure in the multi-level porous iron-based catalyst can also significantly improve the diffusion rate of reactants and products in the multi-level porous iron-based catalyst, reduce the generation rate of carbon deposition, and thus greatly improve the stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The figures are atomic scanning electron microscope comparison images of iron-based catalysts prepared by the method provided in the embodiment of the present invention at different template usage amounts.
[0019] Figure 2 The XRD comparison patterns of the iron-based catalysts prepared by the method provided in the embodiment of the present invention at different template usage amounts are shown.
[0020] Figure 3 The figure is a comparison chart of the pore size distribution of the iron-based catalyst prepared by the method provided by the embodiment of the present invention at different template usage amounts.
[0021] Figure 4 This is a schematic diagram of a four-channel fixed bed reactor used in an embodiment of the present invention.
[0022] Figure 5 This is a schematic diagram of the chromatographic analysis structure used in an embodiment of the present invention.
[0023] Figure 6 The product distribution diagram of the carbon dioxide hydrogenation reaction and the comparison diagram of the carbon dioxide conversion rate are shown in FIG. 1 , which are obtained by using the multi-level porous iron-based catalyst prepared by the method provided in Examples 1 to 4 of the present invention as a catalyst.
[0024] Figure 7 A reaction diagram of a multi-level porous iron-based catalyst for the hydrogenation reaction of carbon dioxide is provided for an embodiment of the present invention. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0026] The present invention provides a method for preparing a multi-level porous iron-based catalyst, which mainly prepares a novel multi-level porous iron-based catalyst by introducing a template agent into a hydrothermal synthesis method. The multi-level porous iron-based catalyst improves the selectivity of methane by adjusting the pore structure while maintaining good CO2 hydrogenation performance, and the stability of the catalyst is also greatly improved.
[0027] Specifically, an embodiment of the present invention provides a method for preparing a multi-level porous iron-based catalyst, comprising the steps of:
[0028] Synthesize iron hydroxide composite crystals, dissolve the template in 80 ml of deionized water and stir for 12 h, so that the template forms smaller droplets and is evenly dispersed in the deionized water to form a milky white suspension; add a soluble iron salt and a precipitant to the milky white suspension in a stirring state at the same time, and continue stirring for 6 h to co-precipitate the iron salt and the precipitant to form porous iron hydroxide, forming an iron hydroxide suspension; after the stirring is completed, pour the iron hydroxide suspension into a 100 ml hydrothermal reactor, and crystallize at a temperature of 150°C to 240°C; after the crystallization is completed, iron hydroxide composite crystals are formed, and the residual precipitant and template are washed three times with deionized water and alcohol respectively by a centrifuge; after the washing is completed, put it into an oven and dry it at a temperature of 80°C for 12 h to obtain iron hydroxide composite crystals, and the iron hydroxide composite crystals are mainly composed of the template and the porous iron hydroxide surrounding the template;
[0029] Calcination treatment: first, the iron hydroxide composite crystals are fully ground into powder, and then placed in a muffle furnace, and calcined at a temperature of 550°C to 700°C for 4 to 9 hours, so that the iron hydroxide in the iron hydroxide composite crystals is decomposed into ferric oxide to form an iron oxide body, and at the same time, the template agent of the iron hydroxide composite crystals is decomposed into gas and volatilized into the surrounding environment, thereby forming a multi-level pore structure with the template agent as the main skeleton structure in the iron oxide body; then grinding, granulation, and 80-120 mesh sieve treatment are carried out in sequence to obtain a catalyst multi-level porous iron-based catalyst with a particle size of 80-120 mesh.
[0030] In the step of synthesizing the composite iron hydroxide crystals, the template agent can not only promote the crystallization process, but also reduce the surface energy of the synthesis system during the crystallization process, making it easy to generate molecules with high specific surface area and small particle size; at the same time, most of the template agents are retained in the pores of the porous iron hydroxide in the form of guest molecules to form composite iron hydroxide crystals. In the step of calcination, the composite iron hydroxide crystals are calcined at high temperature to decompose the template agent contained therein into gas and volatilize it into the surrounding environment, forming pores in the iron oxide body to obtain a regular and empty pore structure, which is similar to the skeleton structure of the template agent.
[0031] Therefore, the template is at least one of triethylamine (TEA), diethylamine (DEA), morpholine (Mor) and tetraethylammonium hydroxide (TEAOH) or any combination thereof. The molar ratio of the iron element in the soluble iron salt to the template is 1:0.5-3. In this embodiment, the hydrothermal reactor is a high-pressure reactor, the template is triethylamine (TEA), and the molar ratio of the template to the iron element in the soluble iron salt is 0, 0.5:1, 1:1, respectively.
[0032] The soluble iron salt is one of iron nitrate, iron sulfate, iron chloride, iron acetate or any combination thereof. The precipitant is an alkaline substance such as sodium hydroxide, potassium hydroxide, ammonia, soluble carbonate, mainly for reacting with the soluble iron salt so that the iron element therein is completely converted into iron hydroxide, so that the addition amount of the precipitant is as long as the soluble iron salt can be completely reacted so that the iron element therein is completely converted into iron hydroxide. In the present embodiment, the soluble iron salt is iron nitrate, the precipitant is ammonia, and the molar ratio of iron nitrate to ammonia is 1:2.
[0033] In the synthesis process of the iron hydroxide composite crystal, the template forms a milky turbid liquid, and the soluble iron salt and the precipitant are co-precipitated on the template to form porous iron hydroxide in situ, and an iron hydroxide suspension is formed under high-speed stirring; the iron hydroxide suspension is placed in a 100 ml high-pressure reactor, using an aqueous solution as the reaction system, and by heating and pressurizing the reaction system (or autogenous steam pressure), a relatively high temperature and high pressure reaction environment is formed, so that the iron hydroxide therein is dissolved and recrystallized and purified, thereby completing the formation of the iron hydroxide composite crystal by the hydrothermal synthesis method. The hydrothermal synthesis method used in this step has the following advantages: (1) the liquid phase is mainly controlled by medium and low temperatures, the process is relatively simple, and a product with complete crystal form, uniform particle size distribution and good dispersibility can be obtained without high temperature treatment, thereby reducing energy consumption; (2) the method has a wide range of applicability, and can prepare both ultrafine particles and single crystals with larger particle sizes, and the obtained products are uniform, high in purity, well crystallized, and the product morphology and size are controllable; (3) the reaction and crystal growth can be effectively controlled during the hydrothermal synthesis process by changing factors such as reaction temperature, pressure, and reaction time. In this embodiment, the crystallization temperature is 200° C. and the crystallization time is 24 h.
[0034] During the calcination process, the iron hydroxide composite crystals are ground into powder, which is beneficial for the iron hydroxide to be fully decomposed into iron oxide during the calcination process. The template agent contained in the iron hydroxide composite crystals is carbonized and decomposed into gas during the high-temperature calcination process, and a pore structure is formed in the body, thereby forming Figure 1 and Figure 2The multi-level porous iron-based catalyst material shown, wherein the molar ratio of the template agent triethylamine to ferric nitrate is 0.5:1 and 1:1, the prepared multi-level porous iron-based catalyst material is marked as Fe-0.5TEA and Fe-1.0TEA. In this embodiment, the calcination temperature is 600°C and the calcination time is 6 h.
[0035] Material structure
[0036] The embodiment of the present invention also provides a method for preparing a multi-level porous iron-based catalyst material that can be used as a high-selectivity catalyst for methane. Figure 1 The small figures a, b, and c in the figure are parallel test TEM images of the multi-level porous iron-based catalyst formed when the template is used in an amount of 0, that is, when no template is used. The product is marked as Fe; the small figures d, e, and f are parallel test TEM images of the product Fe-0.5TEA; and the small figures j, h, and k are parallel test TEM images of the product Fe-1.0TEA. Figure 1 It can be seen that with the addition of template agent TEA, the catalyst surface tends to be smooth and the particle size of the catalyst also shows a decreasing trend. In addition, when the molar ratio of the template agent added is "1", the catalyst particles are in the shape of small spheres. After adding the template agent, the shape of the catalyst particles becomes more regular.
[0037] from Figure 2 It can be seen that the three iron-based catalysts Fe, Fe-0.5TEA, and Fe-1.0TEA show the same characteristic diffraction peaks, which are: 24.1°, 33.1°, 35.6°, 40.8°, 49.5°, 54.1°, 62.5°, and 64.1° (α-Fe2O3, PDF#33-0064), indicating that the introduction of the template has no effect on the bulk structure of the catalyst.
[0038] The pore size distribution of the multi-level porous iron-based catalysts Fe, Fe-0.5TEA and Fe-1.0TEA provided in the embodiments of the present invention was detected by N2 physical adsorption (BET) method. The results are as follows: Figure 3 As shown. Figure 3It can be seen that the pore size distribution of the pure iron-based catalyst without template agent is between 0 and 25 nm, concentrated at 23.87 nm, and the pore size distribution of 30 to 100 nm is speculated to be a pore structure formed by the accumulation of irregular iron oxide particles. After adding the template agent, the pore size distribution of the multi-level porous iron-based catalyst becomes more concentrated. When the molar ratio of the template agent added to the iron element is 0.5, the pore size distribution of the multi-level porous iron-based catalyst is between 0 and 25 nm, concentrated at 13.89 nm; when the molar ratio of the template agent added to the iron element is 1, the pore size distribution of the multi-level porous iron-based catalyst is concentrated between 0 and 15 nm and 20 and 40 nm, respectively, with an average pore size of 7.44 nm. It can be seen that the reduction of the pore size of the multi-level porous iron-based catalyst is one of the reasons why it increases the selectivity of methane as a product of carbon dioxide hydrogenation as a catalyst.
[0039] The specific surface area S of the hierarchical porous iron-based catalysts Fe, Fe-0.5TEA and Fe-1.0TEA was tested by N2 physical adsorption (BET) method. BET , pore volume density V pore and the average pore diameter d pore ; The results are shown in Table 1.
[0040] Table 1 Physical and chemical properties of hierarchical porous iron-based catalysts
[0041]
[0042] It can be seen from Table 1 that with the increase of the amount of template agent, the specific surface area of the hierarchical porous iron-based catalyst gradually increases from 28.26 m 2 .g- 1 Increased to 65.51 m 2 .g- 1 , and its effective pore diameter gradually decreases from 23.87 to 7.44 nm. That is, the amount of template added has little effect on the pore volume density, but has a major impact on the specific surface area and pore size of the hierarchical pore iron-based catalyst.
[0043] Example 1
[0044] An embodiment of the present invention provides a method for preparing a multi-level porous iron-based catalyst, the method comprising:
[0045] Synthesize iron hydroxide composite crystals, weigh 7.6g of triethylamine TEA and dissolve it in 80ml of deionized water and stir for 12h to form a turbid milky white TEA suspension, then add 10.12g of ferric nitrate nonahydrate and 4.8g of ammonium carbonate to the milky white TEA suspension and continue stirring for 6h. After the added substances are completely reacted to form an iron hydroxide suspension, pour the stirred iron hydroxide suspension into a 100ml hydrothermal reactor and crystallize it at a temperature of 200°C for 24h; after the crystallization is completed, use a centrifuge to wash it with deionized water and alcohol three times respectively to wash away the template agent TEA and the precipitant ammonium carbonate remaining on the surface, and after washing, put it into an oven and dry it at a temperature of 80°C for 8h to obtain purified iron hydroxide composite crystals;
[0046] Calcination treatment: First, the purified iron hydroxide composite crystals are put into a grinder for sufficient grinding. After grinding, they are calcined in a muffle furnace at 600°C for 6 hours to completely remove the template agent TEA. Then, they are ground, granulated, and sieved through an 80-mesh sieve to obtain the desired multi-level porous iron-based catalyst.
[0047] This embodiment also provides a multi-level porous iron-based catalyst prepared by the above method, marked as Fe3TEA.
[0048] Example 2
[0049] The embodiment of the present invention provides a method for preparing a multi-level porous iron-based catalyst, which is basically the same as the preparation method provided in Example 1, with the main difference being that the template agent used in this embodiment is 5.8 g of diethylamine (DEA), 6.77 g of ferric chloride, and 4.8 g of precipitant sodium carbonate.
[0050] This embodiment also provides a multi-level porous iron-based catalyst prepared by the above method, marked as Fe3DEA.
[0051] Example 3
[0052] The embodiment of the present invention provides a method for preparing a multi-level porous iron-based catalyst, which is basically the same as the preparation method provided in Example 1, except that the template agent used in this embodiment is 6.55 g of morpholine (Mor) and the precipitant potassium carbonate is 7.46 g.
[0053] This embodiment also provides a multi-level porous iron-based catalyst prepared by the above method, marked as Fe3Mor.
[0054] Example 4
[0055] The embodiment of the present invention provides a method for preparing a multi-level porous iron-based catalyst, which is basically the same as the preparation method provided in Example 1, with the main difference being that the template used in this embodiment is 1.05 g of tetraethylammonium hydroxide (TEAOH) and 11.48 g of ferric sulfate.
[0056] This embodiment also provides a hierarchical porous iron-based catalyst prepared by the above method, labeled as Fe3TEAOH.
[0057] Performance Verification
[0058] The multi-level porous iron-based catalyst and the pure multi-level porous iron-based catalyst (marked as Fe in each figure) provided by Examples 1 to 4 of the present invention can be used as a catalyst for the hydrogenation reaction of carbon dioxide. Figure 4 The existing differential four-channel fixed-bed reaction system shown is used to evaluate the catalytic performance of the multi-level porous iron-based catalyst for catalytic CO2 hydrogenation to olefins and alkanes.
[0059] Reactor for CO2 hydrogenation to produce olefins and alkanes
[0060] The reactor consists of a stainless steel outer tube and a quartz reaction inner tube (inner diameter 4.0 mm). The K-type thermocouple for heating is placed on the stainless steel outer tube where the catalyst bed is located to control the temperature of the three-stage resistance heating furnace. The designed loading is 0.1-0.5 g, the designed reaction pressure is 0.1-5.0 MPa, and the designed temperature is 20℃-500℃.
[0061] Reaction conditions
[0062] The reaction gases are supplied from cylinders, including Ar, H2, CO and 25% CO2 / Ar (volume ratio), and are controlled by thermal gas mass flow meters. The reaction pressure in the reactor is measured by a precision pressure sensor (MKS, 750C12PFF2GA) placed at the reactor inlet.
[0063] The specific experimental process is as follows: Before the performance test, the multi-level porous iron-based catalyst (0.2 g, particle size of 80-120 mesh; diluted with quartz sand of the same mesh size treated with nitric acid, the mass ratio of catalyst to quartz sand is 2:1) was activated for 10 h under 20% CO / Ar or 20% H2 / Ar (50 mL / min), 0.5 MPa and a certain temperature (CO: 350°C, H2: 400°C). After activation, the catalyst was cooled to the reaction temperature of 320°C in the Ar gas flow, and the pressure was increased to 1.55 MPa, and then Ar was switched to the mixed gas required for the CO2 hydrogenation reaction (CO2 / H2 / Ar = 1 / 3 / 3, volume ratio, space velocity is 10000 mLg·cat -1 h. -1) to react.
[0064] Product testing
[0065] The reaction products of carbon dioxide hydrogenation to produce low-carbon olefins are relatively complex, and the main products include hydrocarbons, CO, H2O, etc. After the reaction products are separated by gas-liquid separation, H2O is separated from the gas phase products, and the gas phase products enter Figure 5 The chromatogram shown is used for online analysis. When the gas phase product is sampled, it first passes through a ten-way valve, in which there are two injection loops (1 ml), and the sampling time interval is 55 min / time. The hydrocarbon products are separated by an HP-Plot-Q capillary column (30 m╳0.32 mm╳20 μm), and then detected by a hydrogen flame ionization detector (FID, detection temperature 200 ºC); the other loop is split (split ratio is fixed) and enters two chromatographic columns (TDX-01 1 m╳3 mm, 5A molecular sieve 2 m╳3 mm) for separation and detection. The TDX-01 column mainly separates CO, CO2, and CH4, and then passes through a methane reformer (temperature 330℃) and enters a hydrogen flame ionization detector (FID, temperature 200℃) for analysis; the 5A molecular sieve column is used to separate H2, CO, and CO2, and enters a thermal conductivity detector (TCD detector, bridge flow 60 mA, detection temperature 110℃) for detection. The column temperature was programmed: the initial temperature was 60 °C, maintained for 4 min, then increased to 100 °C at 20 °C / min, maintained for 10 min, and then increased to 220 °C at 10 °C / min and maintained for 15 min.
[0066] Product distribution calculation
[0067] The carbon dioxide concentration is calculated by formula (1-1), and its conversion rate is calculated as follows:
[0068] Formula (1-1);
[0069] The carbon monoxide concentration is calculated by formula (1-2), and the hydrocarbon product selectivity is calculated by formula (1-3):
[0070] Formula (1-2);
[0071] The hydrocarbon selectivity is calculated as follows:
[0072] Formula (1-3);
[0073] Where: X CO2 is the carbon dioxide conversion rate;
[0074] F in is the reactor inlet gas flow rate;
[0075] F out is the reactor outlet flow rate;
[0076] n CO2in is the inlet CO2 concentration;
[0077] n CO2out is the outlet concentration of carbon dioxide;
[0078] S CO is carbon monoxide selective;
[0079] n CO is the carbon monoxide concentration;
[0080] Si is the selectivity of hydrocarbons of component i;
[0081] n CmHn is the m-carbon hydrocarbon concentration.
[0082] The experimental results are as follows Figure 6 As shown, from Figure 6 It can be seen that the selectivity of the multi-level porous iron-based catalyst synthesized by the method provided in Examples 1 to 4 of the present invention to the product methane can reach 83.8%. Compared with the pure iron-based catalyst, the selectivity of the multi-level porous iron-based catalyst provided in the embodiment of the present invention to methane is increased by nearly 42%, and there is not much effect on the conversion rate of carbon dioxide, and the carbon dioxide conversion rate is maintained at about 35%. At the same time, after adding different templates, the selectivity of methane shows a trend of greatly increasing, which shows that the influence of the template on the carbon dioxide hydrogenation performance of the iron-based catalyst has a certain universality.
[0083] The multi-level porous iron-based catalyst Fe3TEA provided in Example 1 was used as the object, and its stability was evaluated using the above catalyst evaluation system. The results are as follows: Figure 7 shown.
[0084] from Figure 7 It can be seen that after 100 h of carbon dioxide hydrogenation reaction, the selectivity of the reaction product methane is still maintained at about 84%; from this, it can be inferred that due to the change in the pore structure in the multi-level porous iron-based catalyst, the diffusion rate of the reactants and reaction products in the crystal is significantly improved, and the formation rate of carbon deposits is reduced, thereby greatly improving the stability of the multi-level porous iron-based catalyst.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A method for preparing a multi-level porous iron-based catalyst, comprising the steps of: Synthesizing iron hydroxide composite crystals: first dissolving a template agent in deionized water to form a template suspension; then simultaneously adding a soluble iron salt solution and a precipitant solution to the template suspension in a stirring state to form an iron hydroxide suspension; then placing the iron hydroxide suspension in a hydrothermal reactor to undergo a crystallization reaction at 150° C. to 240° C. to obtain iron hydroxide composite crystals; wherein, The template agent is at least one of triethylamine, diethylamine, morpholine and tetraethylammonium hydroxide or any combination thereof, and the molar ratio of the iron element in the soluble iron salt to the template agent is 1:0.5-3; Calcination treatment: first grind the iron hydroxide composite crystal into powder to obtain a precursor powder, then place the precursor powder in a muffle furnace and calcine it at 550°C to 700°C for 4 to 9 hours to convert the iron hydroxide therein into iron oxide to obtain a multi-level porous iron-based catalyst, wherein the multi-level porous iron-based catalyst includes an iron oxide body and a pore structure running through the iron oxide body.
2. The preparation method according to claim 1, characterized in that: After the iron hydroxide suspension undergoes a crystallization reaction in the hydrothermal reactor, it is filtered, separated, washed, and dried in sequence to obtain the iron hydroxide composite crystals.
3. The preparation method according to claim 1 or 2, characterized in that: The method also includes the steps of grinding and granulating the multi-level porous iron-based catalyst, and passing the catalyst through a 80-120 mesh sieve to obtain multi-level porous iron-based catalyst particles with a particle size of 80-120 meshes.
4. The preparation method according to claim 1 or 2, characterized in that: The soluble iron salt is one of ferric nitrate, ferric sulfate, ferric chloride, ferric acetate or any combination thereof.
5. The preparation method according to claim 1 or 2, characterized in that: The precipitant is sodium hydroxide, potassium hydroxide, ammonia water or soluble carbonate.
6. A hierarchical porous iron-based catalyst prepared by the preparation method according to any one of claims 1 to 5, characterized in that: It comprises an iron oxide body and a pore structure penetrating the iron oxide body. The average pore diameter of the pore structure is less than 15 nm, and the pore diameter is concentrated in the range of 5 to 14 nm.
7. Use of the multi-level porous iron-based catalyst according to claim 6 in the preparation of methane.
8. Use of the multi-level porous iron-based catalyst according to claim 6 in preparing methane using carbon dioxide and hydrogen as raw materials.
Citation Information
Patent Citations
KR20200083002A